Youth involvement in Dairy value chain: Driving force for Transformation and Sustainability of the Tanzanian Dairy Sector - Lyatuu, Eliamoni T.R.; Komwihangilo, Daniel M.; Msuta, G.; Kelya, Neema; Okeyo Mwai, Ally; Ojango, Julie M.K.; Gebreyohanes, Gebregziabher (2023)
The world population of 8 billion people creates alarm for more food demand, hence the need to increase productivity per available resources. It is pointed out that 50% of Africa’s population are youth below 25 years, meanwhile, 66.1% of total population (61million) of Tanzania youths aged between 15-24 years are participating in the national labour force. Therefore, youth involvement in the dairy value chain is inevitable. Thus, this study used data from AADGG database and complemented with data from mini survey to assess youth involvement in the value chain of dairy production given recent past innovation and technology change. The analysis found that majority of the dairy keepers (55%) are above 45, while youth involvement in dairy business is only 13%. This suggests that if no consented efforts are taken to motivate youths to engage themselves in the dairy value chain, the sector will face a serious labour shortage with time. This study also found that 90.5% of dairy farmers have mobile phones with basic features while only 9.5% have smart phones and majority of this category are youths under 35 years. This is an opportunity since youth with smart phones could easily access new technologies that would transform and sustain livestock sector. However, land being factor in agricultural production, the research found that allocation of 53%, 39% and 8% are for crop, livestock, and pasture and or forest production respectively. The region that allocates major land for livestock is Kilimanjaro (66%) and Arusha (63%) which makes it even harder for youth to access land locked in kihamba style of land ownership. It is therefore concerted effort is recommended to address key constraints though policies, initiatives, strategies, and programme to eliminate challenges and create enabling environment for dairy business that are attractive to youth to invest.